Postmodern Art in Korea, - autor (Contemporary Korean Arts Series, 2015)
This book was written with a critical perspective on postmodernism in Korean contemporary art including painting, sculpture, installation, photography, video and moving image. In Korea, discourse on postmodernism started in the late 1980s, resulting in heated cries for democratization within society. The movement became a trend, as if it was the only alternative to heal all social irregularities and wounds from the past.